2014
DOI: 10.1371/journal.pone.0085803
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Related-Protein Promotes Epithelial-to-Mesenchymal Transition in Prostate Cancer

Abstract: Parathyroid hormone-related protein (PTHrP) possesses a variety of physiological and developmental functions and is also known to facilitate the progression of many common cancers, notably their skeletal invasion, primarily by increasing bone resorption. The purpose of this study was to determine whether PTHrP could promote epithelial-to-mesenchymal transition (EMT), a process implicated in cancer stem cells that is critically involved in cancer invasion and metastasis. EMT was observed in DU 145 prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
3
23
0
2
Order By: Relevance
“…PTHrP is one of the well-known NEPCa derived peptides critical for tumor initiation, growth and metastasis (38). Previous studies showed that PTHrP promoted epithelial-to-mesenchymal transition that is closely connected with metastasis and stemness in PCa (66). It has also been shown that PTHrP enhanced PCa growth via both stabilizing AR and driving a CD11b+Gr1+ cell-mediated positive feedback loop(10, 38).…”
Section: Discussionmentioning
confidence: 98%
“…PTHrP is one of the well-known NEPCa derived peptides critical for tumor initiation, growth and metastasis (38). Previous studies showed that PTHrP promoted epithelial-to-mesenchymal transition that is closely connected with metastasis and stemness in PCa (66). It has also been shown that PTHrP enhanced PCa growth via both stabilizing AR and driving a CD11b+Gr1+ cell-mediated positive feedback loop(10, 38).…”
Section: Discussionmentioning
confidence: 98%
“…TAS-115 also acts on tumor cells PC3 and suppresses cell growth. Previous studies have shown that PC3 produces parathyroid hormone-related peptides (21) and that it is involved in cell migration of PC3 in vitro (22), but the roles of parathyroid hormone-related peptides in the growth and bone metastasis of PC3 in vivo are not known. The action of TAS-115 may be elicited by the suppression of FMS-regulated osteoclastogenesis and MET/VEGFR-dependent cancer cell proliferation in tumor microenvironments of bone tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of invasive ability and mesenchymal phenotype by cancer cells from primary tumors is a requirement for bone metastasis formation [21]. In this contest, several growth factors such as transforming growth factor-β1 (TGF-β1) [22,23], connective tissue growth factor (CTGF) [24], interleukin 11 (IL-11) [25] and parathyroid hormone-related protein (PTHrP) [26], which are critical inducers of skeletal metastases by osteotropic tumors, may play a prominent role in EMT of NETs. Moreover, both the receptor activator of NF-κB (RANK) and C-X-C chemokine receptor type 4 (CXCR4) are involved in the promotion of EMT [27,28,29].…”
Section: Introductionmentioning
confidence: 99%